Synoptic patterns associated with the occurrence of fire foci in the Ecological Station Taim and Campos Neutrais - Brazil - Nascimento, Ana Lucia da Silva (2023)
Abstract: Weather and climate conditions directly influence the occurrence and dynamics of forest fires. And when they occur in environmental preservation regions, they have impacts on biodiversity loss, climate change and water security. This study identified the synotic patterns favorable to the occurrence of hotspot in the Ecological Station Region of the Taim and Campos Neutrais, both located in the extreme south of Brazil. In the study region, humidity deficits are more important than high temperatures, differing from what is described in the literature. Three synoptic patterns were identified: the first presenting negative anomalies of temperature and humidity, established after the passage of a cold front, which has as main contribution to generate a postfrontal stability, associated with the displacement of a high pressure system.  The second and third pattern (64% of wildfire) correspond to the most intense and long-lasting events, which occur in the presence of the South Atlantic Convergence Zone and Humidity Convergence Zone, respectively, and act on the northwest-southeast region of Brazil. These systems favor the slow displacement of a high pressure system over the study region, which contributes to the intensification of a stable environment, favoring moisture deficit and positive temperature anomalies in the study region. The results of this study provide an understanding of how the atmosphere influences the occurrence of wildfire in the study region, and will help in planning the minimization of the impact they can cause in an environmental preservation region